PORTRAYAL OF YOUNG ADULTS IN DYSTOPIAN YOUNG ADULT LITERATURE—HUNGER GAMES TRILOGY - Rana, Ujina; Adhikari, Hari (PEOPLE: International Journal of Social Sciences, 2015)
Young adults shake things up. They exhibit penchant for disturbing the existing institutional systems because their becoming is tantamount to nonconformity. This paper stemmed from the same understanding of the young adults but the conclusion it draws at is that they disrupt the societal codes of behavior and identify themselves as rebels to defy the conventions that plague growth. Dystopia—a subgenre under sci-ficautions us from the wrongs prevalent at present like gender inequality — the offshoot of gender binaries; and if we do not address the pressing issues now, our world might be accelerating towards an abysmal future. This paper is guided by ‘disturbing the universe’ concept propounded by Roberta S. Trites, ‘Utopian Transformation’ by Bradford et al., and Julia Kristeva’s seminal work on ‘Abjection’ theory.